Improving Students' Critical Thinking Ability with Enhanced-Open Learning Approach Using Adaptive Hypermedia - Hernawan Sulistyanto; Nurgiyatna; Harun Joko Prayitno; Sofyan Anif; Sutama; Anam Sutopo (Urecol Journal. Part A: Education and Training, 2022)
The Critical thinking is important in education because it encourages students to gain an understanding of more complex information. High critical thinking skills will lead students to find and conclude their understanding. The prolonged COVID-19 pandemic has made global changes in the implementation of learning. Until now, the learning process is still directed at the online learning model with the help of various Learning Management System (LMS) platforms. Conditions like this have implications for the decline in students' critical thinking skills in various aspects, such as inference, interpretation, explanation, analysis, evaluation, and self-regulation. This study aims at proposing an alternative learning approach, namely the enhanced-open learning model which is used to empower and improve students' critical thinking skills. This learning model was developed using the Research and Development (R&D) method and implemented with an adaptive hypermedia learning application media designed with the Luther development model. The sampling technique used was cluster random sampling on 98 students of informatics education in Surakarta City. The data were analyzed with the prerequisites for normality and homogeneity of the data before the Wilcoxon Signed Rank Test and Mann Whitney U test was carried out to determine the effectiveness of the model. The results of the increase in the gain score obtained from the experiment are in the aspect of interpretation of 93.18%, inference 76.74%, explanation 96.33%, analysis 97, 87%, evaluation 63.01%, and self-regulation 98.13%. Based on the experiments conducted, it is proven that the adaptive open learning approach has a very significant impact on improving students' critical thinking aspects so that it can be concluded that the model is effective in improving students' critical thinking skills.